Dinosaur starts school - Edwards, Pamela Duncan; Allwright, Deborah (Morton Grove, Ill. : Whitman, 2009)
Dinosaur worries about the first day of school, but with the help of a reassuring classmate he finds that school can be fun.
Bulletin (Center for Children's books).
Horn Book.
Kirkus Review.
Bulletin (Center for Children's books), May 2009.
Horn Book, October 2009.
Kirkus Review, June 2009.
Keywords: Dinosaurs -- Juvenile fiction; First day of school -- Juvenile fiction; Worry -- Juvenile fiction; Dinosaurs -- Fiction; First day of school -- Fiction; Worry -- Fiction; Dinosaurs -- Fiction; First day of school -- Fiction; Worry -- Fiction; Picture books for children